2006
DOI: 10.1021/ol0610688
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Enhancement of Enantioselectivity of Biotransformations of β-Hydroxy Nitriles Using a Simple O-Benzyl Protection/Docking Group

Abstract: [Structure: see text] Catalyzed by the Rhodococcus erythropolis AJ270 whole cell catalyst, the O-benzylated beta-hydroxy alkanenitriles underwent remarkably high enantioselective biotransformations, whereas the biotransformations of free beta-hydroxy alkanenitriles gave very low enantioselectivity. The easy manipulations of O-protection and O-deprotection, excellent chemical and enantiomeric yields of biotransformations, along with the scalability render this enzymatic transformation attractive and practical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Studies of biotransformations using R. erythropolis AJ270 whole cells have indicated that the nitrile-degrading enzymes in the cells have high enantioselectivity [24,35,42,44]. In this two-enzyme system, enantioselectivity is largely due to the amidase because nitrile hydratase shows very low enantioselectivity with some substrates [43].…”
Section: R-(+)-2(c-f) (+/-)-1(c-f) S-(-)-3(c-f)mentioning
confidence: 99%
See 3 more Smart Citations
“…Studies of biotransformations using R. erythropolis AJ270 whole cells have indicated that the nitrile-degrading enzymes in the cells have high enantioselectivity [24,35,42,44]. In this two-enzyme system, enantioselectivity is largely due to the amidase because nitrile hydratase shows very low enantioselectivity with some substrates [43].…”
Section: R-(+)-2(c-f) (+/-)-1(c-f) S-(-)-3(c-f)mentioning
confidence: 99%
“…Two hundred microliters of isopropyl alcohol was added to resolve the precipitation after a process of ether extraction (700 ll) and blowdrying. Five microliters of the solution was used in the high-performance liquid chromatography (HPLC) assay as previously reported [23,24,44]. All products were characterized by their spectral data.…”
Section: Regio-and Stereoselectivity Of Amidasementioning
confidence: 99%
See 2 more Smart Citations
“…The unprotected aliphatic, 3‐aminobutyronitrile 2 was obtained commercially and protected amino acid derivatives were prepared from this by employing standard protection protocols from literature as outlined in the supplementary information . The aromatic analogue 3‐amino‐3‐phenylpropionitrile 6 was prepared by adapting a procedure developed by Brady et al , to employ sodium triacetoxyborohydride in place of sodium cyanoborohydride for enamine reduction as .…”
Section: Resultsmentioning
confidence: 99%